THE EFFECT OF WORK MOTIVATION AND WORK ABILITY ON THE WORK PRODUCTIVITY OF PALM OIL HARVESTERS AT PTPN IV ADOLINA AFDELING II PLANTATION - Eden Efrin Tambunan; Purjianto (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Work productivity is one of the important factors in determining the operational success of oil palm plantation companies, especially in the harvesting section. This study aims to analyze: (1) the effect of work motivation on work productivity; (2) the effect of work ability on work productivity; and (3) the effect of work motivation and work ability simultaneously on the work productivity of harvesters at PTPN IV Regional I Adolina Plantation Afdeling II. This study uses an explanatory research method with a quantitative approach. The research sample consisted of 48 oil palm harvesters selected using a saturated sampling technique. Data were obtained through questionnaires and analyzed using descriptive analysis, validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and coefficients of determination (R²) with the help of SPSS version 23. The results of the study indicate that work motivation and work ability simultaneously have a significant effect on work productivity. Partially, work motivation does not have a significant effect on work productivity, while work ability has a positive and significant effect on work productivity. Therefore, the company needs to improve the work ability of harvesters through technical training, job coaching, and periodic evaluations to increase harvester work productivity.